2021
DOI: 10.1002/ange.202105861
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Ladder‐Type Heteroheptacene‐Based Nonfullerene Acceptors Enabled by Asymmetric Cores with Enhanced Noncovalent Intramolecular Interactions

Abstract: Nonfullerene acceptors (MQ3, MQ5, MQ6) are synthesized using asymmetric and symmetric ladder‐type heteroheptacene cores with selenophene heterocycles. Although MQ3 and MQ5 are constructed with the same number of selenophene heterocycles, the heteroheptacene core of MQ5 is end‐capped with selenophene rings while that of MQ3 is flanked with thiophene rings. With the enhanced noncovalent interaction of O⋅⋅⋅Se compared to that of O⋅⋅⋅S, MQ5 shows a bathochromically shifted absorption band and greatly improved carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Further, a larger ESP distinction between the donor and acceptor promoted a stronger intermolecular electric field formation, thereby promoting efficient charge generation. [55,56] Therefore, 2D asymmetric cyclo-alkyl chain modification on central core preferably enhances intermolecular interaction and exciton dissociation, hence boosting FF and PCE.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Further, a larger ESP distinction between the donor and acceptor promoted a stronger intermolecular electric field formation, thereby promoting efficient charge generation. [55,56] Therefore, 2D asymmetric cyclo-alkyl chain modification on central core preferably enhances intermolecular interaction and exciton dissociation, hence boosting FF and PCE.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[ [39][40][41] On the one hand, unlike the sp 3 -hybridized carbon atom, the sp 2 -hybridized nitrogen has stronger electron-donating ability. The lone pair electrons in the p-orbital of the nitrogen atom can be delocalized along the whole π-conjugated system, which not only improves intramolecular charge transfer effect to extend absorption, but also reduces the reorganization energy to achieve a small energy loss.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Recent studies have shown that sp 2 ‐hybridized nitrogen‐ bridged fused‐ring cores are a fascinating class of building blocks for the construction of novel NFAs with excellent photophysical and electronic properties, which are difficult to achieve in previous ITIC‐like NFAs with sp 3 ‐hybridized carbon‐bridged fused‐ring cores. [ 39‐41 ] On the one hand, unlike the sp 3 ‐hybridized carbon atom, the sp 2 ‐hybridized nitrogen has stronger electron‐donating ability. The lone pair electrons in the p‐orbital of the nitrogen atom can be delocalized along the whole π‐conjugated system, which not only improves intramolecular charge transfer effect to extend absorption, but also reduces the reorganization energy to achieve a small energy loss.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[16][17][18][19] The energy levels involving the highest occupied molecular orbital (HOMO) energy level and the lowest unoccupied molecular orbital (LUMO) energy level of the third component are crucial factors to constitute effective charge-transport channels and avoid generating charge recombination center or traps in ternary blends. [20][21][22][23][24] Meanwhile, a higher LUMO energy level of the acceptor or a deeper HOMO energy level of the donor for the third component can provide opportunities to reduce voltage loss in ternary OSCs relative…”
Section: Introductionmentioning
confidence: 99%